2021
DOI: 10.1111/jphd.12489
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life in US adults with type 2 diabetes

Abstract: Keywordsoral health-related quality of life; oral health; quality of life; type 2 diabetes; United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
0
11
3
Order By: Relevance
“…Following previous studies ( 15 , 23 ), the composite score generated from OHIP-7 was used to construct two OHRQoL measures—the severity of perceived poor OHRQoL and the prevalence of poor OHRQoL. The severity of perceived poor OHRQoL was based on a summative score, ranging from 0 to 28, generated from seven questions in OHIP-7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following previous studies ( 15 , 23 ), the composite score generated from OHIP-7 was used to construct two OHRQoL measures—the severity of perceived poor OHRQoL and the prevalence of poor OHRQoL. The severity of perceived poor OHRQoL was based on a summative score, ranging from 0 to 28, generated from seven questions in OHIP-7.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies examined the impact of periodontal diseases on the OHRQoL between patients with and without diabetes and found mixed findings ( 11 13 ). Others identified risk factors associated with the poor OHRQoL of diabetic patients and found several risk factors, including, but not limited to, dry mouth sensation, the use of a removable prosthesis, untreated dental caries, periodontal disease, unmet denture needs, low income, and poor oral hygiene ( 14 , 15 ). Based on the national data with a sample of 2,945 community dwellers in the United States, the study found that diabetic patients were more likely to experience poorer OHRQoL than those without diabetes ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…BMI, WC, TG, and systolic BP were higher in the obese group than in the non-obese group, confirming the recruitment of participants for the study who experienced adverse impacts on OHRQoL. Levels of FPG were not significantly different among all the studied groups, excluding the influence of DM on lower OHRQoL [ 16 ].…”
Section: Discussionmentioning
confidence: 69%
“…Our search of the literature found no studies that have directly explored OHRQoL in older persons with obesity. Most studies reported OHRQoL in adults or older patients with metabolic syndrome (MS), diabetes mellitus (DM), or chronic kidney disease (CKD) [ 16 , 17 , 18 ]. The OHRQoL of patients with MS, DM, or CKD whose status had an obese component tended to be negatively impacted [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation